The scientific expedition of Joao da Silva Feijo to the Cabo Verde Islands (1783-1796) and the tribulations of his herbarium - Gardere, Mathieu L. (2019)
Joao da Silva Feijo (1760-1824), Portuguese naturalist taking part in the Philosophical Journeys under the patronage of the Portuguese Crown, led the first scientific expedition devoted exclusively to the study of the Natural History of the Cabo Verde Islands between 1783 and 1796. On behalf of the Royal Museum of Natural History and Botanical Garden of Ajuda in Lisbon, Feijo made the first extensive plant collections (1783-1789) on all of the islands that together with his manuscripts offer a glimpse of the flora of Cabo Verde, as it existed at the end of 18th century. This study provides unique data on the legacy of Feijo's collections, with details of his expedition through the Cabo Verde Islands. His plant collections, nameless for a long time and scattered in different Herbaria, were reunited specifically for this study. Moreover, the manuscripts related to the plant collections are discussed, and the link between the Feijo's determinations and the current scientific names were established. A numbering for this herbarium is proposed here, based on the Linnaean sexual system in order to facilitate future studies of this historical collection. Each specimen has been labelled with some precious information from archives (collector, date) to pay tribute to Feijo and to break the two century-long silence of his collection. Finally, the Feijo herbarium, and its various tribulations over the years are described and explained.